Modal verbs in legal English - Pelíšková, Veronika (2006)
The subject of my dissertation is the issue of modal verbs in legal English. The dissertation is based on a parallel corpus. My aim is to conduct research into legal English documents and analyze the use of modal verbs in context and look at the frequency with which they occur. Furthermore, I will deal with their Czech equivalents and discuss their semantics